Knowledge management in Indonesia small and medium enterprises (SMEs): a conceptual model - Adhiatma, Ardian; Fachrunnisa, Olivia (2016)
In this global market, the growth of Small to Medium Enterprises (SMEs) has improving. Thus, the competition among SMEs becomes more rapid which requires them to put more efforts in maintaining their existance and development.Facing this issue, organizations should turn their entrepreneural orientation from money oriented to innovation oriented.To innovate better, HRs in an organization should be knowledgeable hence theorganization has to advance its knowledge management.This research aims to examine the relationship of entrepreneurial orientation, knowledge management, total quality management, and organizational innovation performance. Theoretical model drawn from literature review/survey is presented in this study. Therefore, this research can be one of new literatures which study about this issue from new frame. Thus, future research is presented in this study.